2015
DOI: 10.1007/s10910-015-0533-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel global and local 3D atom-based linear descriptors of the Minkowski distance matrix: theory, diversity–variability analysis and QSPR applications

Abstract: A new family of alignment-free 3D descriptors based on TOMOCOMD-CARDD framework has been designed, namely 3D-linear indices. In this report, we have proposed the use of a generalized form of the geometric pairwise atom-atom Electronic supplementary material The online version of this article (123 J Math Chem distance matrix as structural information matrix. This matrix, denominated as nonstochastic, uses as matrix form of linear maps as well as their algebraic transformations: stochastic, double stochastic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 113 publications
(160 reference statements)
0
6
0
Order By: Relevance
“…This section is dedicated to assessing the introduction of the new truncation method based on FMFs, specifically in the molecular encoding. To this end, the QuBiLS‐MIDAS 3D‐MDs were considered, with the purpose of performing cheminformatics studies related to variability analysis, linear independence and modeling. The QuBiLS‐MIDAS 3D‐MDs are based on multilinear (tensor) algebraic forms (maps).…”
Section: Validation Of the Smoothed Spherical Truncation Methods Basedmentioning
confidence: 99%
“…This section is dedicated to assessing the introduction of the new truncation method based on FMFs, specifically in the molecular encoding. To this end, the QuBiLS‐MIDAS 3D‐MDs were considered, with the purpose of performing cheminformatics studies related to variability analysis, linear independence and modeling. The QuBiLS‐MIDAS 3D‐MDs are based on multilinear (tensor) algebraic forms (maps).…”
Section: Validation Of the Smoothed Spherical Truncation Methods Basedmentioning
confidence: 99%
“…The QuBiLS‐MIDAS framework is one of the novel strategies introduced for the MDs computation based on atoms (LOVIs) . This framework enables to determine geometric molecular descriptors (3D‐MDs) based on multi‐linear algebraic maps.…”
Section: Practical Example: Gowawa Operator‐based Qubils‐midas Molecumentioning
confidence: 99%
“…This framework enables to determine geometric molecular descriptors (3D‐MDs) based on multi‐linear algebraic maps. These 3D‐MDs are the only ones that codify chemical information between two atoms using several metrics other than the Euclidean distance,, as well as structural information regarding the relations between three and four atoms by means of multi‐metrics . Several studies have demonstrated that these 3D‐MDs encode information with high variability and linear independence with regard to other MDs reported, and, in addition, they yield superior performances in QSAR modeling ,…”
Section: Practical Example: Gowawa Operator‐based Qubils‐midas Molecumentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the previous idea, recently the 3D N - linear algebraic molecular descriptors have been introduced as a novel mathematical procedure for computing the structural features of chemical compounds [ 24 26 ]. These MDs employ the bilinear , quadratic and linear algebraic maps [ 27 ] to codify information between atom-pairs by using several (dis - )similarity metrics [ 25 ].…”
Section: Introductionmentioning
confidence: 99%